2019
DOI: 10.1002/adma.201900690
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and Perspectives on Triplet‐Material‐Based Organic Photovoltaic Devices

Abstract: Organic photovoltaic cells (OPVs) have attracted broad attention and become a very energetic field after the emergence of nonfullerene acceptors. Long-lifetime triplet excitons are expected to be good candidates for efficiently harvesting a photocurrent. Parallel with the development of OPVs based on singlet materials (S-OPVs), the potential of triplet materials as photoactive layers is explored. However, so far, OPVs employing triplet materials in a bulk-heterojunction have not exhibited better performance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 119 publications
(64 reference statements)
1
54
0
Order By: Relevance
“…[ 13 − 18 ] Therefore, in order to reduce both voltage loss and NG recombination, the Δ E ST needs to be minimized (Figure 1b). [ 22,23 ]…”
Section: Figurementioning
confidence: 99%
“…[ 13 − 18 ] Therefore, in order to reduce both voltage loss and NG recombination, the Δ E ST needs to be minimized (Figure 1b). [ 22,23 ]…”
Section: Figurementioning
confidence: 99%
“…The reduced HOMO energy level could be mainly originated from the increased steric hindrance effect induced by the bulky dfppy unit on the iridium (Ir) complex. [ 1,25 ] In addition, the LUMO energy levels of the iridium (Ir) complex‐based polymers were slightly higher than that of control polymer PM6‐Ir0. Regardless of that, the energy levels of these designed polymers matched well with the acceptor Y6 (HOMO/LUMO = −5.65/−4.10 eV).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Peng and co‐workers developed an incorporated strategy of platinum (II) complexation, which can effectively regulate the crystallinity and molecular packing order of polynitrogen heterocyclic polymer donors, optimize the corresponding blend morphologies, as 10% (molar ratio related to the s‐tetrazine block) of Pt(Ph) 2 (DMSO) 2 was added to the polymer backbone of (4,8‐bis(5‐((2‐butyloctyl)thio)‐4‐fluorothiophen‐2‐yl)benzo[1,2‐b:4,5‐b′]dithiophene‐alt‐3,6‐bis(4‐octylthiophen‐2‐yl)‐1,2,4,5‐tetrazine) polymer donor (Pt0), the J sc and FF were increased from 25.10 to 26.45 mA cm −2 and from 64.9% to 76.3%, respectively, and the PCE of the Pt10‐based photoactive layer was finally improved from 13.03% (Pt0 polymer donor) to 16.35%. [ 25 ] According to these previous results, [ 1,38–44 ] it can be easily concluded that, introducing suitable third components or units into the polymer backbone of high performance photovoltaic materials is a promising approach to improve the blend microstructure, balance the above‐mentioned three competitors, and thus to increase the device performance with a higher PCE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Enlarging spin-orbit coupling (SOC) by chemically or physically introducing heavy atoms into the conjugated materials has been proposed to enhance ISC rate. [25][26][27] So far, some research studies have been done on triplet material-based OPVs (T-OPVs) [28][29][30][31] and the highest PCE for small-molecule Ir complexes is 3.81%. 32 However, the voltage losses in T-OPVs were rarely investigated.…”
Section: Introductionmentioning
confidence: 99%